Locus of Control, Penerimaan Auditor atas Dysfunctional Audit Behavior dan Intention to Quit - Anita, Rizqa; Nanda, Satria Tri; Zenita, Raisya; Abdillah, Muhammad Rasyid (Jurnal Dinamika Akuntansi dan Bisnis, 2018)
This study aims to examine personal characteristics of auditor acceptance of dysfunctional audit behavior. More specifically, it aims to investigate locus of control on intention to quit and auditor acceptance of dysfunctional audit behavior. This study surveys public accounting firm in Sumatera with a total of107 respondents. Data analysis was performed by using Structural Equation Modeling-Partial Least Square (PLS-SEM). The results show that locus of control has positive influence on intention to quit and auditor acceptance of dysfunctional audit behavior. In addition, it is also suggested that the effect of locus of control on auditor acceptance of dysfunctional audit behavior is indirectly influenced through intention to quit.